Numerical Flow Simulation and Cavitation Prediction in a Centrifugal Pump using an SST-SAS Turbulence Model - Ennouri, M.; Kanfoudi, H.; Bel Hadj Taher, A.; Zgolli, R. (Journal of Applied Fluid Mechanics, 2019)
The paper handles the subject of the modelling and simulation of the flow inside a centrifugal pump through non-cavitating and cavitating conditions. Operating under cavitation state is so perilous to a pump and can considerably reduce its lifetime service. Hence, to provide highly reliable pumps, it is essential to comprehend the inner flow of pumps. The investigated centrifugal pump comprises five backward curved-bladed impeller running at 900 rpm. The modelling process started with an unsteady numerical analysis under non-cavitating conditions to validate the numerical model and the solver comparing with the available testing data. Due to high Reynolds numbers, turbulence effects have been taken into account by unsteady RANS methods using an SST-SAS turbulence model. The obtained pump performances were numerically compared with the experimental ones, and the outcome shows an acceptable agreement between both. The temporal distribution of the internal flow parameters such as pressure and velocity was then studied. Furthermore, basic investigations of cavitating flow around 3D NACA66-MOD profile using a recently developed and validate cavitation model was established. The verification of the numerical simulation validity was based on comparing calculated and experimental results and presented good agreement. Finally, a 3D simulation of the inception of the cavitating pocket inside the centrifugal pump is performed to analyze the impact of the cavitation in the decrease of the head and efficiency.